2020
DOI: 10.21203/rs.3.rs-34365/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dexmedetomidine as an adjunct to local anesthetics in nerve block relieved pain more effectively after TKA: A meta-analysis of randomized controlled trials

Abstract: Background: Dexmedetomidine has shown potential in pain control in patients undergoing Total Knee Arthroplasty (TKA). However, the combination of nerve block and dexmedetomidine may be a preferred alternative for postoperative analgesia after TKA. The aim of this study was to perform a meta-analysis on existing randomized controlled trials (RCTs) to determine the efficacy and safety of dexmedetomidine as an adjunct to local anesthetics in nerve block after TKA.Methods: A literature survey was conducted in the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…32 A meta-analysis also revealed that it is effective and safe for dexmedetomidine as an adjunct to local anesthetics in nerve block in TKA to relieve postoperative pain, decrease total opioid consumption, prolong analgesic duration, and increase patient satisfaction without increasing related complications. 33 Our results were similar with that showed in the above two studies. All of these results indicated that dexmedetomidine added local anesthetics decreased the opioid consumption and provide a better postoperative analgesia.…”
Section: Discussionsupporting
confidence: 93%
“…32 A meta-analysis also revealed that it is effective and safe for dexmedetomidine as an adjunct to local anesthetics in nerve block in TKA to relieve postoperative pain, decrease total opioid consumption, prolong analgesic duration, and increase patient satisfaction without increasing related complications. 33 Our results were similar with that showed in the above two studies. All of these results indicated that dexmedetomidine added local anesthetics decreased the opioid consumption and provide a better postoperative analgesia.…”
Section: Discussionsupporting
confidence: 93%
“…Ultrasound-guided continuous femoral nerve block for postoperative analgesia is widely used in clinical practice. However, due to incomplete obturator nerve block and incomplete puncture in the ultrasound image, it is difficult to control the depth of the needle insertion and often difficult to achieve a satisfactory analgesic effect [4,5]. e "Shamrock method" is a new ultrasonic-guided lumbar plexus nerve block method with in-plane needle insertion, in which a low-frequency probe is placed at the head side of the iliac crest of a patient to obtain ultrasound cross-sectional images of the lumbar spine and paravertebral structure, including ultrasound images of the lumbar plexus nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Pan L et al also concluded that pain scores significantly decreased at different time points postoperatively when dexmedetomidine was used an adjunct to nerve blocks. 18 Motor strength was important factor to keep track of for the patients as well as for the surgeons because early rehabilitation is essential and helpful for the success of TKR. Dexmedetomidine combined with local anesthetics in nerve block could increase motor strength compared to local anesthetics alone.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine combined with local anesthetics in nerve block could increase motor strength compared to local anesthetics alone. 18 This is likely due to the fact that dexmedetomidine can inhibit the local anesthetics to penetrate the motor fibre. Motor strength on both sides in group C is significantly higher than group A.…”
Section: Discussionmentioning
confidence: 99%